Analysis of the Effectiveness and Efficiency of the Realisation of the Regional Revenue and Expenditure Budget at the Regional Financial Management Agency of the District Wonogiri Period 2019 - 2021 - Slamet Riyadi; Sri Wijiastuti; Darsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the level of effectiveness and efficiency of the use of regional revenue and expenditure budgets at the Wonogiri district financial management agency. The object of this research is the Regional Financial Management Agency (BPKD) of Wonogiri District. The reason for choosing this location is because it is the author's hometown, making it easier for the author to obtain the data needed during the research process. the variables studied are: -RAPBD (Regional Revenue and Expenditure Budget Plan) -APBD (Realization of Regional Revenue and Expenditure Budget for the Period of 2019 to 2021. The results of the study concluded that the level of effectiveness of regional income at the Wonogiri District regional financial management agency for the 2019-2021 budget year had reached the budget target that had been set but had met the effective criteria. Then, judging from the level of efficiency of regional spending at the Wonogiri District regional financial management agency for the 2019 to 2021 budget years, it is considered less efficient.